PENGARUH VARIASI KADAR ASAM BASA TERHADAP WAKTU LARUT GRANUL EFFERVESCENT EKSTRAK HERBA MENIRAN (Phyllanthus niruri L.) - Indarto Indarto; Kiki Puspitasary (Jurnal Health Sains, 2022)
One of the plants that have the potential to be developed as traditional medicine is the green meniran herb (Phyllanthus niruri L.). The results showed that meniran herbs contain lignin and terpenoid compounds that have potential as antibacterials. People use meniran as a medicine for itching by drinking boiled water of meniran, lowering glucose and diuretic levels, and increasing body resistance. Meniran herbs were extracted by the maceration method with 96% ethanol as solvent. Then refluxed for 6 hours with the same solvent. Meniran herb extract was formulated into effervescent granules with varying levels of acid sources, namely citric acid, and tartaric acid, with a ratio of FI (0.5 g: 1.5 g), FII (1 g: 1 g), FIII (1.5 g: 0.5 g). Effervescent granules were evaluated physically including flow rate, angle of repose, drying shrinkage, and dissolving time. The results of the study showed that the extract of the meniran herb contained flavonoids, alkaloids, sterols and triterpenoids, saponins, polyphenols, and tannins. The flow rate of each formula increased with the addition of tartaric acid in the formula, the higher the tartaric acid added, the faster the flow time. The results of the dissolution time showed that the greater the concentration of sodium bicarbonate, the longer the dissolution time of the effervescent granule preparation. Based on the results obtained, all formulas have a pH value of 4-5.